Commercial Greenhouse Production: Greenhouse cucumber - Marr, Charles W. (My University, 1995)
This publication describes the commercial production of greenhouse cucumbers.
MF2075_1995_02
Keywords: MF2075; Lawn and Garden; fruits and vegetables; equipment and structures; MF